Exposure and dose assessment to particle components among an elderly population. (February 2015) - Almeida-Silva, M.; Almeida, S.M.; Pegas, P.N.; Nunes, T.; Alves, C.A.; Wolterbeek, H.T.
Abstract: People spend the majority of their time indoors and the composition and toxicity of indoor particles is very complex and present significant differences comparing with outdoor aerosols. Consequently, ambient particles cannot represent a real exposure. The aim of this work was to determine the daily exposure and the daily inhaled dose to particle components of elders living in Elderly Care Centers. A questionnaire was applied to 193 institutionalized elders in order to achieve their daily time pattern and to define the micro-environments where PM10 and its components (carbonaceous components and trace elements) were assessed. Daily exposure was calculated by integrating the elder's time spend in each micro-environment and the concentration of the pollutants for the period of interest. This parameter, together with the inhalation rate and the standard body weight, were used to calculate the daily inhaled dose. PM10 daily exposure and daily inhaled dose ranged between 11 – 16 μg m −3 and 20 × 10 −3 – 28 × 10 −3  μg kg −1, respectively. This work not only allowed a fully quantification of the magnitude of the elders exposure, but also showed that the assessment of the integrated exposure to PM components is determinant to accomplish the dose inhaled by elders living in ECCs. Highlights: Elderly spend 95% of their time indoors. Indoor air quality was closely linked to personal exposure. The exposure and the inhaled dose of the studied elders differed significantly. The contribution of each indoor micro-environment depended on the particle constituents and respective sources.